Practical guide to using 6Mo austenitic stainless steel - Davison, Ralph M.; Redmond, James D. (Nickel Development Institute, 1988)
This booklet gives information on the metallurgy, crevice corrosion, and chloride stress corrosion cracking resistance, design, and fabrication as well as specifications and commercial product of alloys 254 SMO,™ AL-6X,™ AL-6XN,™ 1925 hMO (26-6MO) and 20 MO-6.™
"Reprinted from: Materials performance, December 1988."
Keywords: Austenitic stainless steel.; elektronické knihy; electronic books